A closer look at the Test of Personal Intelligence (TOPI). (1st June 2017) - Mayer, John D.; Panter, A.T.; Caruso, David R.
Abstract: Personal intelligence involves the capacity to reason about personality and personality-related information. Studying ability-based measures of personal intelligence creates a virtuous cycle of better measurement and better theoretical understanding. In Study 1 ( N = 10, 318), we conduct an item-level analysis of the Test of Personal Intelligence (TOPI) to explore people's problem-solving abilities in the area. Personal intelligence divided into a Consistency-Congruency factor that concerned understanding traits and their associated behaviors, and a Dynamic-Analytic factor that involved understanding personality processes and goals. The finding cross-validated in Study 2 ( N = 8, 459). In Study 3 ( N = 384), we examined correlates of the two factors. Understanding the abilities involved in personal intelligence may help us to educate people about how to better solve problems about personality. Highlights: We examined the Test of Personal Intelligence across three studies. Factor analyses in Study 1 ( N = 10, 318) supported a two-factor model of the test. People high in Factor 1 reason about the consistency of personality. People high in Factor 2 reason about personality dynamics. In Studies 2 and 3 the scales replicated ( N = 8, 459); predicted outcomes ( N = 384).